Penerapan Metode Activity-Based Costing (ABC) dalam Mengukur Biaya Produksi dan Meningkatkan Efisiensi Operasional - Lucky Mahesa Yahya; Helda Marlin Ala; Loso Judijanto; Irma Hakim; Asdi Asdi (Journal of Economic, Bussines and Accounting (COSTING), 2024)
The ABC method emerged as a response to the weaknesses of traditional methods, such as the production volume-based costing method. The purpose of this study was to analyze the Application of the Activity-Based Costing (ABC) Method in Measuring Production Costs and Improving Operational Efficiency. The research method used is a literature study or Library Research with a qualitative approach. The literature used is literature from research results or reviews presented in national and international scientific articles that are related to accounting. All articles used are sourced from the electronic literacy data search engine Mendeley and Google scholar. Based on the literature review of several articles on the results and discussion, the conclusions that can be drawn are: The application of the Activity-Based Costing (ABC) method has a significant impact on measuring production costs and increasing the company's operational efficiency. Keywords: Activity-Based Costing; Production Cost; Operational Efficiency